Fermentation process optimization and chemical constituent analysis on longan (Dimocarpus longan Lour.) wine. (1st August 2018) - Liu, Guoming; Sun, Jian; He, Xuemei; Tang, Yayuan; Li, Jiemin; Ling, Dongning; Li, Changbao; Li, Li; Zheng, Fengjin; Sheng, Jingfeng; Wei, Ping; Xin, Ming
Highlights: Proline, alanine, glutamic acid and aspartic acid contents were high in longan wine. Ethyl lactate content was the highest among 63 volatile aromas in longan wine. Main functional components in longan wine were polysaccharides. 10–30 kDa polysaccharides exhibited the highest hypoglycemic and DPPH-scavenging activities. Abstract: Based on single factor and orthogonal experiments, optimal fermentation conditions for longan wine were Saccharomyces cerevisiae strain of Lalvin KD, juice content of 70% and alcohol content of 10°. Sixteen amino acids were detected. Proline, alanine, glutamic acid and aspartic acid contents were relatively high. Sixty-three volatile aroma compounds were identified using solid-phase micro extraction and gas chromatography (SPME-GC). Ethyl lactate content was the highest, followed by octanoic acid ethyl ester, isoamyl alcohol and decanoic acid ethyl ester. Main functional components were polysaccharides. Longan wine polysaccharide (LWP) with molecular weight 10–30 kDa exhibited the highest hypoglycemic and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging activities. 10–30 kDa polysaccharides mainly consisted of glucose, mannose, galactose, arabinose, galacturonic acid and glucuronic acid in molar ratio of 167.72:3.38:3.13:3.46:2.33:1. Infrared and nuclear magnetic resonance spectra confirmed that the sugar ring of 10–30 kDa polysaccharides was in the 〈beta〉-configuration.